Professionalism Stage of Educators in Private Islamic Collage: Student Perspective Analysis - Susanti, Weti; Vanessa, Anadya Diva; Akhir, Nur Afzan Bt Md; Utami, Rahmi Dwi; Putri, Santri Dewi; Anas, Khairul (International Journal of Multidisciplinary Research of Higher Education, 2024)
Professionalism in education has a strong correlation with high educational standards. The figure of a professional educator will affect the learning process of how to teach effectively and honestly, and this will also be significant because the professionalism of educators is an important factor in determining the quality of education in higher education. This study aims to examine how students perceive the professionalism of educators in private Islamic universities through the application of Islamic values. This research uses an explanatory mixed method design. Data sources were taken from fifteen informants through in-depth interviews selected using purposive sampling technique, all informants consisted of active students who chose Islamic education majors in one of the Private Islamic Universities in Indonesia. All interview results were then analyzed thematically using VOSviewer software and Microsoft Excel. The results of the analysis indicate that students have diverse views on the professionalism of educators who have been reviewed from four aspects of competence as educators, namely: i) pedagogical competence, ii) personality competence, iii) social competence, iv) professional competence. The implications of this study indicate the need to improve the quality of education through continuous training for educators, with a focus on integrating Islamic principles in teaching methods and curriculum development. The results of this study provide important insights for policy makers and Islamic higher education institutions in an effort to improve the professionalism of educators and the quality of education in accordance with Islamic values.